2020
DOI: 10.1083/jcb.201903127
|View full text |Cite|
|
Sign up to set email alerts
|

ERdj8 governs the size of autophagosomes during the formation process

Abstract: In macroautophagy, membrane structures called autophagosomes engulf substrates and deliver them for lysosomal degradation. Autophagosomes enwrap a variety of targets with diverse sizes, from portions of cytosol to larger organelles. However, the mechanism by which autophagosome size is controlled remains elusive. We characterized a novel ER membrane protein, ERdj8, in mammalian cells. ERdj8 localizes to a meshwork-like ER subdomain along with phosphatidylinositol synthase (PIS) and autophagy-related (Atg) prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 55 publications
1
17
1
Order By: Relevance
“…Nine different ERjs reside in the human ER ( Table 1 ) [ 79 , 80 , 81 , 130 , 145 , 146 , 147 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 ]. As the name infers, ERjs are characterized by individual J-domains, which allow interaction with BiP via the bottom of its NBD and, to do so, contain four α-helices (helices I–IV) with a loop region containing a highly conserved tripeptide of histidine, proline, and aspartic acid (HPD motif) located between helices II and III.…”
Section: Gating Of the Sec61 Channel By Bipmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine different ERjs reside in the human ER ( Table 1 ) [ 79 , 80 , 81 , 130 , 145 , 146 , 147 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 ]. As the name infers, ERjs are characterized by individual J-domains, which allow interaction with BiP via the bottom of its NBD and, to do so, contain four α-helices (helices I–IV) with a loop region containing a highly conserved tripeptide of histidine, proline, and aspartic acid (HPD motif) located between helices II and III.…”
Section: Gating Of the Sec61 Channel By Bipmentioning
confidence: 99%
“…Only ERj3 through ERj6 appear to be involved in protein folding under physiological as well as ER stress conditions and in ERAD. The other ERjs play more specialized roles in ER protein import (Sec63/ERj2 and ERj1) [ 79 , 80 , 81 , 102 , 143 , 145 , 146 , 147 , 151 ] or ER-phagy (ERj8) [ 234 ]. Thus, there is redundancy also at the level of the ERjs, which may explain the non-lethal phenotype of loss of Sec63 function that is associated with polycystic liver disease (see below).…”
Section: Gating Of the Sec61 Channel By Bipmentioning
confidence: 99%
“…The ERdj proteins are a family of proteins harboring the DNAJ domain that cooperate with the molecular chaperones and play diverse roles in the ER [54][55][56]. Recently, we analyzed their uncharacterized member, ERdj8 [12]. ERdj8 was partially colocalized with PIS-enriched ER subdomains and also partially colocalized with Atg proteins (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…The size of autophagosomes varies from a few hundred nanometers in diameter to over a micrometer [ 10 , 11 ]. Recently, we have reported that the ER resident membrane protein, ERdj8/DNAJC16, is involved in the size determination of autophagosomes [ 12 ]. Herein, we introduce recent advances in the relationship between autophagosome formation and endoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 99%
“…This dynamic interaction with unfolded proteins prevents their unfavorable interactions and co-aggregation with other folding intermediates. Nucleotide exchange factors and J-domain containing co-chaperones (ERdj1-8) modulate the activity of BiP and help recruiting clients [7,8]. When a protein fails to fold in the ER, it can be subjected to the ER-associated degradation (ERAD) machinery and degraded via the ubiquitin-proteasome system [9].…”
Section: Introductionmentioning
confidence: 99%